2014
DOI: 10.1302/0301-620x.96b8.33644
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of failure for cephalomedullary nailing of proximal femoral fractures

Abstract: The purpose of this study was to identify factors that predict implant cut-out after cephalomedullary nailing of intertrochanteric and subtrochanteric hip fractures, and to test the significance of calcar referenced tip-apex distance (CalTAD) as a predictor for cut-out. We retrospectively reviewed 170 consecutive fractures that had undergone cephalomedullary nailing. Of these, 77 met the inclusion criteria of a non-pathological fracture with a minimum of 80 days radiological follow-up (mean 408 days; 81 days t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
180
8
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(208 citation statements)
references
References 31 publications
16
180
8
4
Order By: Relevance
“…Both biomechanical and clinical data suggest that CM nails have a mechanical advantage over extra-medullary implants in their ability to resist femoral shaft medialization and varus malunion, and this has led to the increased use of CM nails for hip fractures [8][9][10][11]. However, recent studies showed that there is still a high revision rate for unstable hip fractures treated with CM nails mainly due to cut-out of the lag screw [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Both biomechanical and clinical data suggest that CM nails have a mechanical advantage over extra-medullary implants in their ability to resist femoral shaft medialization and varus malunion, and this has led to the increased use of CM nails for hip fractures [8][9][10][11]. However, recent studies showed that there is still a high revision rate for unstable hip fractures treated with CM nails mainly due to cut-out of the lag screw [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It supports the findings from previous studies that the inferior placement of the lag screw reduces cutout. 7,16,1,18 It provides the first clinical evidence behind the validity of CalTAD as a better predictor of cutout than TAD in biaxial CM. It questions the validity of the length of AR screw as a predictor of failure of biaxial CM nail and suggests further investigations to study its impact on such constructs.…”
Section: Resultsmentioning
confidence: 97%
“…9 This may be due to a shorter operating time, reduced visible intraoperative blood loss, and improved walking ability in unstable hip fractures associated with CM nail. 1 Current CM concepts may be classified as monoaxial and biaxial. In monoaxial systems, special lag screw designs have been introduced to strengthen rotational stability, whereas in biaxial systems, a second element, an AR screw, is meant to achieve this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). This complication is encountered after fixation with either intramedullary [18,19] or extramedullary devices [20]. Cut out has been associated with the Tip Apex Distance (TAD) Index, which represents the sum of distances measured in mm in both anteroposterior and lateral radiographs from the centre of the femoral head to the top of the lag screw [21].…”
Section: Cut-outmentioning
confidence: 99%